GERAKAN MENJADI MUZAKKI DAN TERBENTUKNYA KELUARGA SAKINAH; PENYULUHAN UNTUK IBU-IBU DI DESA NEGARA BATIN KECAMATAN JABUNG LAMPUNG TIMUR (Studi Kasus Praktikum Profesi Makro Bimbingan Penyuluhan Islam (BPI) Fakultas Dakwah dan Ilmu Komunikasi UIN Syarif Hidayatullah Jakarta 2024) - Halim, M. Jufri; Rahman, Abdul (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2024)
This research is in order to oversee the implementation of the 2024 BPI Student Macro Professional Practicum Program, Islamic Extension Guidance Study Program which is being implemented in Negara Batin Village, Jabung District, East Lampung Regency, Lampung Province, mainly regarding the student program of the Zakat Empowerment group and the Sakinah Family group. What is your role in building a Sakinah Family through the practice of Zakat, Infaq and Shadakah? The aim of this research is to see the impact and influence of the combined Zakat and Sakinah Family Empowerment program. This research uses a qualitative descriptive method, with the theory of zakat empowerment and the Sakinah family. The conclusion of this research, describing the programs implemented by BPI 2024 Macro Professional Practicum students which were carried out in Negara Batin Village, Jabung District, East Lampung, can be said to have had a very good impact, and can even have a positive influence on families. Considering that a number of families are known to be able to plan according to the knowledge they have to build a Sakinah family, namely a family that is based on the habit of sharing, starting from the habit of giving shadakah, zakat and becoming a love for ZIS, at a higher level they hope to be proud to be able to become muzakki in the future.